High‐Rate CO2 Electroreduction to C2+ Products over a Copper‐Copper Iodide Catalyst. Issue 26 (17th May 2021) - Li, Hefei; Liu, Tianfu; Wei, Pengfei; Lin, Long; Gao, Dunfeng; Wang, Guoxiong; Bao, Xinhe
Abstract: Electrochemical CO2 reduction reaction (CO2 RR) to multicarbon hydrocarbon and oxygenate (C2+ ) products with high energy density and wide availability is of great importance, as it provides a promising way to achieve the renewable energy storage and close the carbon cycle. Herein we design a Cu‐CuI composite catalyst with abundant Cu 0 /Cu + interfaces by physically mixing Cu nanoparticles and CuI powders. The composite catalyst achieves a remarkable C2+ partial current density of 591 mA cm −2 at −1.0 V vs. reversible hydrogen electrode in a flow cell, substantially higher than Cu (329 mA cm −2 ) and CuI (96 mA cm −2 ) counterparts. Induced by alkaline electrolyte and applied potential, the Cu‐CuI composite catalyst undergoes significant reconstruction under CO2 RR conditions. The high‐rate C2+ production over Cu‐CuI is ascribed to the presence of residual Cu + and adsorbed iodine species which improve CO adsorption and facilitate C−C coupling. Abstract : A Cu‐CuI composite catalyst achieves a remarkable C2+ partial current density of 591 mA cm −2 at −1.0 V vs. RHE, substantially higher than Cu or CuI alone. It is ascribed to the presence of residual Cu + and adsorbed iodine species which improve CO adsorption and facilitate C−C coupling during CO2 electroreduction.